HIV infection among child population of the Republic of Bashkortostan - A. B. Latypov; D. A. Valishin (LLC "Diagnostics and Vaccines", 2019)
The aim of the study: to assess the incidence, prevalence, structure by sex and transmission routes of HIV infection among the child population of the Republic of Bashkortostan.A study of data on HIV infection among children 0-17 years in the republic for 2014-2018 was conducted.Results: the average incidence of HIV infection for 2014-2018 in the age group 0-14 years was 3.4 ± 0.4, 15-17 years - 8.7 ± 1.1, 0-17 years - 4.1 ± 0.4 per 100,000 child population of the corresponding age, the average prevalence of HIV infection at the age of 0-14 years - 26.6 ± 1.1, 15-17 years - 17.2 ± 3.1, 0-17 years - 25.2 ± 1.3 per 100,000 child population of the corresponding age. In 2018 compared to 2014 the incidence of HIV infection in the age group 0-14 years increased by 35.3%, 15-17 years - by 45.0%, 0-17 years - by 36.8%, the prevalence - in the age group 0-14 years increased by 27.4%, 15-17 years - 2.6 times, 0-17 years - by 38.3%. In 96.8% of HIV infections in children aged 0-14 years occurred as a result of perinatal transmission of the virus. Among children 0-14 years of age, 55.8% of cases were diagnosed with HIV infection at the age of 0-1 years. In 29.4% of children 0-14 years with perinatal transmission of HIV infection, the disease was detected at the age of 2 years and older. At the age of 15-17 years, sexual transmission of HIV infection prevailed - 90.9%, female adolescents accounted for 78.2%. In 21.8% of cases, HIV infection was detected in adolescents of the female sex during pregnancy follow-up, in 9.1% in the examination in connection with the consumption of drugs.